Nano-hydroxyapatite mineralized silk fibroin porous scaffold for tooth extraction site preservation. Issue 10 (October 2019) - Nie, Ling; Zhang, He; Ren, Aishu; Li, Yuzhou; Fu, Gang; Cannon, Richard David; Ji, Ping; Wu, Xiaohong; Yang, Sheng
Highlights: We fabricated nano-hydroxyapatite mineralized porous silk fibroin (MSF) scaffold and applied MSF scaffold for SD rat tooth extraction site preservation. MSF scaffold had good hydrophilcity and biocompatibility and could provide a favorable physical environment to induce cell viability in vitro . MSF grafts depicted greater performance of inducing the bone formation and reducing the height of alveolar bone resorption after tooth removal, making it be a great potential biomaterial for tooth extraction site preservation. Abstract: Objective: To fabricate a novel nano-hydroxyapatite mineralized silk fibroin (MSF) scaffold in order to diminish the resorption of alveolar ridge and accelerate new bone formation within tooth sockets. Also, to investigate the biocompatibility and osteogenic ability of the MSF in vitro, and the effect of site preservation of the MSF graft in post-extractive sockets in vivo . Methods: SEM, EDX, FTIR and XRD were used to analyze the mineral crystals deposited on the silk fibroin (SF) surface. Pre-osteoblasts (MC3T3-E1) were seeded on SF and MSF scaffolds. Cell viability, distribution and differentiation were examined using a live-dead assay, histological analysis and Alizarin Red S staining. Furthermore, prepared grafts (SF or MSF scaffold) were implanted into the maxillary right first molar sockets of Sprague Dawley rats for 6 weeks and newly formed bone tissue was analyzed by micro-CT and histological examination. Results: The SEM, EDX, FTIR and XRD analysis demonstrated that granulate nano-hydroxyapatite (nHA) crystals were uniformly distributed on the SF scaffold. In addition, the MSF hydrophilicity measured by water contact angle and swelling ratio was superior to plain SF scaffold. The effect of nHA inorganic crystals on osteogenic differentiation of MC3T3-E1 cells indicated the MSF scaffolds improved osteogenesis. Furthermore, MSF grafts induced more bone formation and reduced the height of alveolar bone resorption after tooth extraction. Significance: The MSF scaffold partially simulated the structure and composition of natural bone matrix. It induced osteogenic differentiation of MC3T3-E1 cells in vitro, and also promoted new bone regeneration in tooth extraction sockets in vivo, indicating it is a biomaterial with great potential for tooth extraction site preservation.